PREVALENCE OF POSITIVE CULTURE SAMPLES AND ASSOCIATED MICROORGANISMS AMONG CULTURES SAMPLES IN MICROBIOLOGY LABORATORY AT UGANDA MARTYRS HOSPITAL LABORATORY LUBAGA KAMPALA UGANDA. - Nakiboneka, Winnie (Student's Journal of Health Research Africa, 2024)
INTRODUCTION: Microbiology culture before initiation of antimicrobial therapy is considered to be the gold standard for diagnosis of bacterial and fungal infections. In addition to facilitating the differentiation of harmless bacterial and fungal contaminants from bacterial pathogens. Accurate identification of specific bacterial and fungal species aids in the selection of antimicrobial and antifungal drugs. Failure to perform cultures and interpret results correctly may lead not only to diagnostic errors but to therapeutic failures as well. The study documents the Prevalence of positive culture samples and the microorganisms associated with the positive cultures at Uganda Martyrs Hospital Laboratory Lubaga Kampala METHODOLOGY: A cross-sectional study of randomly selected result reports was analyzed retrospectively for growth and the associated isolated organism from the positive samples. RESULTS: 100 culture sample results were reviewed. The prevalence of positive culture sample is 40%. This laboratory reported that 40 (40%) specimens had a positive culture with 34 (85%) were bacterial and 6 samples (15%) were fungal. All the fungal growth was confirmed Candida Albicans. Escherichia coli 47.9%, Enterococcus Faecalis 14.7%. Staphylococcus Haemolyticus 17.6% Staphylococcus Aureus 8.2%. Klebsiella Pneumoniae, Streptococci Viridans, Citrobacter Freundii and Acinetobacter Baumannii each account for 2.9%. CONCLUSIONS: The prevalence of 40% positive culture samples is a high prevalence that shouldn’t be overlooked. Escherichia Coli is the most commonly encountered microorganism in this laboratory. RECOMMENDATIONS: Hand and oral hygiene coupled with vigorous environmental decontamination should be re-emphasized for adequate pathogen control. CLINICAL RELEVANCE: These preventive measures will control the spread of related infections and the rampant use of antibiotics. Controlled use of antibiotics plays a role in minimizing the raising antimicrobial resistance which is a major global health concern.